APA DAN MENGAPA ILMU INFORMASI? - Ida Fajar Priyanto (Jurnal Kajian Informasi dan Perpustakaan, 2013)
Information science is an interdisciplinary science which deals with the interpretation of the information and matters relating to the cognitive process, the context and the phenomenon of information. Information science is still a new science that was founded in 1950 and currently still in bloom. At first the science of information is closely connected to the system, but is now turning to human factors in information, including information behavior and ergonomics.Ilmu Informasi adalah ilmu interdisipliner yang membahas tentang interpretasi informasi dan berbagai hal terkait dengan proses kognitif, konteks dan fenomena informasi. Ilmu informasi masih merupakan ilmu baru yang berdiri sejak tahun 1950an dan saat ini masih dalam masa berkembang. Pada awalnya ilmu informasi sangat erat hubungannya dengan sistem, namun kini beralih ke faktor manusia dalam informasi, termasuk perilaku informasi dan ergonomi.